2018
DOI: 10.1099/jmm.0.000646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial susceptibility of Clostridium difficile isolated from hospitals during a 4-year period in China

Abstract: MLST typing revealed a wide variety of STs causing CDI, while ST-54 was the most common ST. All of the isolates were susceptible to metronidazole and vancomycin, while the resistance rates varied for the other antibiotics tested. There were no changes in the trends for the STs and antibiotic susceptibility profiles over 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
23
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
11
23
3
Order By: Relevance
“…Analyses of sequences were made in Unipro UGENE 1.28 (UniPro, Russia), and MLST profiles were obtained from the public database (https://pubmlst.org/cdifficile/). Three ribotypes (RTs) and strain types (STs) ( Table 1), which have all been described in human patients with CDI around the world, were obtained [32,33]. Our results corroborate the findings of recent studies, which have shown substantial similarities between human and dog C. difficile isolates, suggesting possible zoonotic transmission [34,35].…”
supporting
confidence: 88%
“…Analyses of sequences were made in Unipro UGENE 1.28 (UniPro, Russia), and MLST profiles were obtained from the public database (https://pubmlst.org/cdifficile/). Three ribotypes (RTs) and strain types (STs) ( Table 1), which have all been described in human patients with CDI around the world, were obtained [32,33]. Our results corroborate the findings of recent studies, which have shown substantial similarities between human and dog C. difficile isolates, suggesting possible zoonotic transmission [34,35].…”
supporting
confidence: 88%
“…It was confirmed that patients in the CDI group had a prolonged hospital stay. In a previous study, ST-35 and ST-3 were among the most prevalent types in the hospital (21), and were the two predominant types in this study. The current researchers speculated that transmission events may exist, although discriminatory bacterial typing techniques, such as whole genome sequencing, are needed to validate these findings.…”
Section: Discussionsupporting
confidence: 67%
“…Although the CDT+ strain appeared less frequently in Asia, this was not the first report of this toxin genotype in China. ST5 accounted for 83.7% of binary toxin gene-positive strains in a survey conducted by Chen et al [40] in 2018. Data on C. difficile strains in clade 3 with binary toxins are not well documented in mainland China.…”
Section: Discussionmentioning
confidence: 99%